Saúde emocional, qualidade de vida e bem-estar docente: o reconhecimento do outro na esfera da docência universitária - Vieira, Maricélia de Almeida (2021)
This dissertation is part of the research line "Teaching, knowledge and teacher training", of the Postgraduate Program in Education at the Federal University of Santa Maria (UFSM). The research aimed to understand the relationships that permeate Emotional Health, Quality of Life at Work (QLW), and the well-being of university professors and, as they are understood as an integrating and (trans) forming factor in the university context. In the perspective of this proposal, one enters the higher teaching context and their experiences in the work context, which possibly impact the professors' psychological aspect. In this sense, the proposal for theoretical and methodological cuts is given by the qualitative approach MYNAIO (2016), narrative interview (BAUER AND GASKEL, 2015) and JOSSO (2015); content analysis (BARDIN, 2016). The theoretical contribution allows us to go from SANT & # 39; ANNA AND KILIMNIK (2011) at QVT, WALTON (1974), FRANCE (2010); to JESUS (2004)'s Well-Being; Professor knowledge TARDIF (2014); and teaching work by BOLZAN, ISAIAS, MACIEL (2011), DEJOURS (2015), FREITAS (2013) in order to weave other reflections that make the research proposal viable. And finally, the recognition of the other that surrounds the outline of the theoretical context of HONNETH (2003) and by the forms of Recognition in different spheres of the theory, and based on the understanding of the theory in GADAMER (1999). The narratives enabled us to observe how university professors understand the relationships that permeate the guiding questions of Emotional Health, Quality of Life at Work (QWL), and Well-Being in the university context. In addition, the professors' narratives showed the relationships of trajectories and their actions in the current context, reframing and transforming the actions and mental representations of the actions carried out as university professors. Thus, emphasizing the concepts covered in the research in relation to the university professor's work context is essential, so that it becomes necessary to reflect in a collective context, to obtain a better understanding of Emotional Health, Well-Being, related to the professor's QWL, that way that educators, start to make better use of their time in educational institutions.